Expressive vocabulary in English and Malay among primary one school children: a comparison between boys and girls - Tang, Swee Gek (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This research compared the expressive vocabulary in English and Malay between male and female students. This research also compared the overall students' perfonnance of the expressive vocabulary in English and Malay. Data on 11 government primary schools (N = 866) were collected using random sampling. The research showed that females perfonned better than males in the both English and Malay expressive vocabulary. However, the females perfonned better in Malay expressive vocabulary than in English expressive vocabulary. These results highlight the influence of the order oflanguage acquisition (e.g. first language versus second language learning).